Harmonization of Halal Tourism Regulations and The Digital Sharia Economy: A Perspective from Islamic Economic Law - Triyono Adi Saputro; Diana Setiawati; Nur Rizqi Febriandika; Awalia Rina Rahmawati; Wahyu Tri Mohamad Firdaus (Universitas Muhammadiyah Purwokerto, 2026)
Indonesia’s halal tourism industry has grown rapidly, ranking first in the Global Muslim Travel Index for two consecutive years (2023–2024), alongside the accelerating national digital sharia economy, now valued at USD 99 billion in 2025. Surakarta, a city of significant cultural and religious importance with a large domestic tourist base, has yet to establish specific regulations integrating halal tourism standards with the digital Sharia economy ecosystem, creating a legal gap amid growing market potential. This study aims to analyze the current state of halal tourism and digital Sharia economy regulations in Surakarta and to formulate an ideal harmonization model within the framework of Islamic economic law. This normative legal research employs statutory, conceptual, and case-based approaches, utilizing primary legal materials (legislation and DSN-MUI fatwas), secondary materials (academic literature and official reports), and tertiary materials, analyzed qualitatively and descriptively through mapping, gap analysis, and synthesis. The findings indicate that the regulatory vacuum in Surakarta reflects the local government’s failure to position hifz al-din and hifz al-mal as structural variables in economic policy, compounded by weak cross sectoral institutional coordination. The study proposes a harmonization model grounded in maqāşid al-sharī’ah, expanding the conventional four-pillar framework (regulatory harmonization, standardization, multi-stakeholder synergy, and sustainability orientation) with a fifth pillar digital interoperability that links halal certification databases, tourism business data, and national sharia marketplace ecosystems. This model offers a transferable framework for other culturally and religiously significant “middle-tier” cities pursuing the development of a halal tourism identity in Indonesia’s digital era.